2015
DOI: 10.1002/iub.1391
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic decline of β‐cell function with age in euglycemic nonobese diabetic mice parallels diabetes onset

Abstract: A gradual decline in insulin response is known to precede the onset of type 1 diabetes (T1D). To track age-related changes in the β-cell function of non-obese diabetic (NOD) mice, the most commonly used animal model for T1D, and to establish differences between those who do and do not become hyperglycemic, we performed a long-term longitudinal oral glucose tolerance test (OGTT) study (10–42 weeks) in combination with immunofluorescence imaging of islet morphology and cell proliferation. We observed a clear bip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
12
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 56 publications
7
12
0
Order By: Relevance
“…This involved collection of a large number of samples (collected at 6, 11, 16, 21, and 26 weeks of age from mice whose glycemia was monitored and retrospectively designated as T1D progressors or non-progressors depending on whether they became hyperglycemic or not by the end of the study). Diabetes onset in these NOD mice was typical and similar to what we have obtained previously [33,34], starting around 12 weeks of age with approximately 60% of females and 30% of males becoming diabetic by week 26 (Figure S2A). At the end of the study (week 26 of age), representative samples from 3F + 3M non-progressors (control) and 4F + 4M T1D progressors were subjected to global metabolomics, which identified and quantified a large number of metabolites (676 and 706 in blood and feces, respectively).…”
Section: Resultssupporting
confidence: 88%
“…This involved collection of a large number of samples (collected at 6, 11, 16, 21, and 26 weeks of age from mice whose glycemia was monitored and retrospectively designated as T1D progressors or non-progressors depending on whether they became hyperglycemic or not by the end of the study). Diabetes onset in these NOD mice was typical and similar to what we have obtained previously [33,34], starting around 12 weeks of age with approximately 60% of females and 30% of males becoming diabetic by week 26 (Figure S2A). At the end of the study (week 26 of age), representative samples from 3F + 3M non-progressors (control) and 4F + 4M T1D progressors were subjected to global metabolomics, which identified and quantified a large number of metabolites (676 and 706 in blood and feces, respectively).…”
Section: Resultssupporting
confidence: 88%
“…Female NOD mice are used extensively as a model for human autoimmune T1D [12][13][14][15][16][17]. Numerous studies have shown that under specific-pathogen-free conditions typically 70-90% of female NOD mice develop diabetes spontaneously by 45 weeks of age [9,11]. Consistent with this, we found an 80% diabetes incidence rate in a population of 126 female NOD mice aged up to 43 weeks (Figure 1).…”
Section: Discussionsupporting
confidence: 83%
“…In addition, injection of total SPLs obtained from new-onset diabetic NOD mice showed attenuated levels of α-cell proliferation 3 weeks after transfer when compared to β-cell proliferation (figure 3B). A similar finding was reported by Cechin et al 27. Together, these data suggest that immune cell-derived soluble factors provide preferential stimulatory effects favoring β cells.…”
Section: Introductionsupporting
confidence: 90%